2015
DOI: 10.3390/children2040403
|View full text |Cite
|
Sign up to set email alerts
|

Young Age at Diagnosis of Type 1 Diabetes Is Associated with the Development of Celiac Disease—Associated Antibodies in Children Living in Newfoundland and Labrador, Canada

Abstract: Objectives: The objectives of this study were to establish the prevalence of positive antibodies to endomysium (EMA) and tissue transglutaminase (tTG) in children with type 1 diabetes living in Newfoundland and Labrador (NL), and to examine clinical features associated with positive antibodies. Methods: Patients were recruited from the pediatric diabetes clinic. One hundred sixty-seven children with type 1 diabetes from the 280 children followed at the clinic were prospectively screened for celiac disease usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(38 reference statements)
0
4
0
Order By: Relevance
“… 8 The rate of EMA or TTG antibody positivity in T1DM patients was found to be 9.8% to 20.6% in different studies, and it was found to be 18.6% (78 patients) in our study. 2 , 9 , 10 In the literature, the rate of spontaneous normalization of antibodies reported by Unal et al 11 was 23.3%, and it was found to be approximately 35.4% in the study by Waisbourd-Zinman et al 12 …”
Section: Discussionmentioning
confidence: 94%
“… 8 The rate of EMA or TTG antibody positivity in T1DM patients was found to be 9.8% to 20.6% in different studies, and it was found to be 18.6% (78 patients) in our study. 2 , 9 , 10 In the literature, the rate of spontaneous normalization of antibodies reported by Unal et al 11 was 23.3%, and it was found to be approximately 35.4% in the study by Waisbourd-Zinman et al 12 …”
Section: Discussionmentioning
confidence: 94%
“…Since the serological tests became available for screening, studies have shown that patients with T1DM also have positive tests in the absence of CD diagnosis [ 24 25 26 27 ]. In a pediatric study, TTG IgA was found to be transient or to fluctuate in patients with T1DM and became normal when repeated later and most had an infiltrative lesion or entirely normal mucosa upon histological confirmation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the well-recognized concerns of the serological tests is the positive serology found in individuals who had normal mucosa [ 13 14 ], though in occasional cases, this might be the result of patchy distribution of disease with inadvertent biopsies of normal mucosa, or ‘latent CD’ if patients eventually developed villous atrophy later [ 22 23 ]. This is particularly notable in T1DM patients with a high positive rate of TTG IgA without mucosal villous atrophy [ 24 25 26 27 ]. The TTG IgA antibody is routinely performed to screen children with T1DM diagnosis for CD whether symptomatic or asymptomatic [ 12 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation